Three-dimensional database of subcortical electrophysiology for image-guided stereotactic functional neurosurgery. - Finnis, K.W (IEEE Transactions on medical imaging)
We present a method of constructing a database of intraoperatively observed human subcortical electrophysiology. In this approach, patient electrophysiological data are standardized using a multiparameter coding system, annotated to their respective magnetic resonance images (MRIs), and nonlinearly registered to a high-resolution MRI reference brain. Once registered, we are able to demonstrate clustering of like interpatient physiologic responses within the thalamus, globus pallidus, subthalamic nucleus, and adjacent structures. These data may in turn be registered to a three-dimensional patient MRI within our image-guided visualization program enabling prior to surgery the delineation of surgical targets, anatomy with high probability of containing specific cell types, and functional borders. The functional data were obtained from 88 patients (106 procedures) via microelectrode recording and electrical stimulation performed during stereotactic neurosurgery at the London Health Sciences Centre. Advantages of this method include the use of nonlinear registration to accommodate for interpatient anatomical variability and the avoidance of digitized versions of printed atlases of anatomy as a common database coordinate system. The resulting database is expandable, easily searched using a graphical user interface, and provides a visual representation of functional organization within the deep brain.